Concepção de sistema de controle de RCC em canteiros de obras de edifícios de múltiplos andares - Lobo, Mariana Giovani (2019)
This work aimed to develop a support system for planning and control of waste construction (WC) for construction sites of multi-floors buildings. For this, started from a macro analysis, verifying the Management Plans required by the National Solid Waste Policy (NSWP) at the national, state and municipal levels until reaching the research outline: construction sites. The data for the composition of the National and State overview was obtained from recent information from the Ministry of the Environment (ME), reports and official documents from federal and state agencies. For the situation about the Integrated Solid Waste Management of Municipal Plans (ISWMMP) analyzed the municipal laws of each one of the 645 municipalities of the State of São Paulo. In addition, along with this analysis to this analysis identified the same laws that required the use of the Waste Transport Control (WTC) document, provided for in Conama Resolution Nº. 307/2002. For the next stage of the research, a questionnaire was developed to analyze the reality of the sites constructions and obtain tool suggestions for the proposed system. The questionnaire was applied at four different companies building multi-floors buildings. As initial results, it was found that the Union does not have its National Plan official, over the States more than half already have their plans prepared and for the municipalities of São Paulo, the reality found was different from that provided by the Green Blue Municipality Program (GBMP). Currently, less than half of the municipalities - 48% - have their ISWMMP elaborated and instituted by law, and under this same premise it was found that only 13% of the municipalities are required to use the WTC. About the case studies, they revealed that big generators miss a solid WC database to consult. The system was designed based on the suggestions and analysis of the reality shared by the four builders. It was concluded that the big generators do a lot and seek by the fact that they have certifications such as ISO 9001 and PBQP-H. The proposed system is a complete control tool that seeks greater integration of WC management related activities in the site construction to assist the big generators. Its differential is the sharing of data between users that will compose a consolidated and easily accessible database.